A Comparative Study of Antimicrobial Activity of Curcuma amada and Alpinia galanga of Zingiberaceae Family - Rama Rao, M.; Bhaskar Reddy, I.; Raja Gopal, S.V.; Bhaskar, D.; Ramana, T. (Asian Journal of Chemistry, 2010)
The antimicrobial activity of different solvent extracts of Curcuma amada and Alpinia galanga against gram positive and gram negative bacteria and some fungal strains was studied. The results showed that the broad spectrum of activity against all tested microorganisms. The total phenolics of C. amada are ranging from 29.0 to 59.5 and A. galanga from 28.4 to 56.5 mg GAE per g of dry weight.